Modernizing Talisayan Regional General Hospital's Holistic Inpatient Services: The Role of Human Resources, Infrastructure, and Physician Attrition with Innovation as a Key Driver - Andik Irwanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research examines the effects of human resource competence, facilities and infrastructure, and doctor turnover on the quality of inpatient services within Talisayan Regional Public Hospital, located in Berau Regency, employing innovation as a mediating variable. The study was conducted using an explanatory quantitative methodology, involving a total population of 3,082 inpatient individuals, from which a sample of 97 respondents was selected through purposive sampling, adhering to a 10% margin of error as determined by the Slovin formula. Data collection was executed using Likert-scale questionnaires and analysed employing Partial Least Squares-Structural Equation Modelling utilising SmartPLS 4. The results indicate that human resource competence exerts a positive influence on innovation (0.283), while facilities and infrastructure also demonstrate a positive impact (0.422). In contrast, doctor turnover negatively influences innovation (-0.449). In terms of its direct effects on comprehensive service, human resource competence has a slight non-significant impact (0.074), facilities and infrastructure show a significant effect (0.185), and doctor turnover presents a negative non-significant influence (-0.091). Innovation: A comprehensive service significantly benefits from innovation (0.408). Innovation significantly contributes to comprehensive service (0.408). Indirectly, the positive impacts of Human Resource Competence (0.115) and Facilities and Infrastructure (0.172) on Comprehensive Service are significant, whereas Doctor Turnover again exhibits a negative effect (-0.183). Penelitian ini menyelidiki dampak dari Kompetensi Sumber Daya Manusia, Sarana Prasarana, dan Turnover Dokter terhadap pelayanan paripurna untuk pasien rawat inap di RSUD Talisayan, dengan Inovasi berfungsi sebagai variabel intervening. Mengaplikasikan metodologi kuantitatif eksplanatori, studi ini melibatkan 97 responden yang diambil dari populasi 3.082 pasien rawat inap dengan menggunakan teknik purposive sampling dan pengumpulan data melalui kuesioner Likert. Hasil analisis menunjukkan adanya pengaruh signifikan Kompetensi SDM terhadap Inovasi sebesar 0,283, pada Sarana Prasarana sebesar 0,422, dan dampak negatif dari Turnover Dokter sebesar -0,449. Pengaruh langsung terhadap pelayanan paripurna memperlihatkan bahwa Kompetensi SDM tidak signifikan dengan nilai 0,074, sedangkan Sarana Prasarana signifikan pada 0,185, dan Turnover Dokter juga tidak signifikan dengan nilai -0,091. Inovasi menunjukkan dampak positif yang signifikan terhadap pelayanan paripurna dengan nilai 0,408. Secara tidak langsung, Kompetensi SDM memiliki pengaruh positif yang signifikan sebesar 0,115, Sarana Prasarana sebesar 0,172, dan Turnover Dokter memberikan pengaruh negatif yang signifikan sebesar -0,183 terhadap pelayanan paripurna melalui Inovasi.